TOWARD SUSTAINABLE ENVIRONMENT GOALS OF PRME: ANALYSING WASTE SEPARATION BEHAVIOUR IN SBM ITB USING EXPANDED MODEL OF THEORY OF PLANNED BEHAVIOR - Putri, Utami S; Wisesa, Anggara (Journal of Business and Management, 2018)
Abstract. School of Business and Management ITB as the only Principles of Responsibility and Management Education (PRME) signatory in Indonesia, is committed to achieve Sustainable Development Goals (SDGs) by implementing PRME values and principles. However, according to PRME Sharing Information Progress Report of SBM ITB, among 12 issues of sustainability that become the focus of PRME implementation, researcher found a lack of action SBM ITB took on waste management issue. The use of traditional waste management system implemented by SBM ITB doesn’t go along with the value of environmental sustainability. Therefore, strategic actions must be designed to overcome waste management problem as well as to achieve environmental sustainability in SBM ITB. This study aims to analyse waste separation behaviour in SBM ITB Ganeca Campus and provide recommendations to construct strategic planning in realizing environmental sustainability in SBM ITB. After collecting the questionnaires from 100 samples from students and staff of SBM ITB, research hypotheses were analysed using Partial Least Square Structural Equation Modelling (PLS-SEM). The results of this study indicate that environmental knowledge and perceived moral obligation influence attitude in separating waste. While attitude and perceived behavioural control significantly influence waste separation intention, which has also been tested as a factor that influences individual’s behaviour in separating waste. Keywords: Principles of Responsible Management Education, Pro-environmental Behaviour, Sustainable Development Goals, Environmental Sustainability, Waste Separation Behaviour.